The Phenomenical Character of Dispositional Properties - González Estrada, Allan (2023)
This paper delves into the nature of dispositional properties, such properties has been of a recent interest in the philosophy of mind and metaphysical debates, however its role and nature has not been clear. I shall argue that such properties determine our behavior once the phenomenal and intentional properties have been realized by the relevant brain states, thus, it is explore the role of disposition in a way that determine our behavior base on the epistemic role of consciousness to represent our beliefs and desires, the base of this argument lies on the idea that most of our mental properties are phenomenal,  and our perceptual process is regulate via an indirect realism, hence will be argue that what it is required for dispositional properties are the realization first of phenomenonological-intenciontal properties.